2022
DOI: 10.1021/acs.jpcb.2c04960
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Vibrating Sharp-Edge Spray Ionization Augments Field-Free Ionization Techniques to Promote Conformer Preservation in the Gas-Phase for Intractable Biomolecular Ions

Abstract: Field-free capillary vibrating sharp-edge spray ionization (cVSSI) is evaluated for its ability to conduct native mass spectrometry (MS) experiments. The charge state distributions for nine globular proteins are compared using field-free cVSSI, field-enabled cVSSI, and electrospray ionization (ESI). In general, for both positive and negative ion mode, the average charge state (q avg) increases for field-free cVSSI with increasing molecular weight similar to ESI. A clear difference is that the q avg is signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Recently it has been shown that this allows improved preservation of the structure of fragile proteins relative to nESI. 48,49 These unique attributes (softness, ionization efficiency, and simplicity/accessibility) of cVSSI suggest that it may be possible and indeed useful to couple native MS with in-droplet HDX for examining challenging biomolecular solution structures including coexisting conformers and structural transformations. In seeking to apply new techniques to the study of the biomolecular structure, this work builds upon the seminal experiments of Derrick and Williams and their coworkers who studied the nature of in-droplet processes for biomolecules using theta capillaries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it has been shown that this allows improved preservation of the structure of fragile proteins relative to nESI. 48,49 These unique attributes (softness, ionization efficiency, and simplicity/accessibility) of cVSSI suggest that it may be possible and indeed useful to couple native MS with in-droplet HDX for examining challenging biomolecular solution structures including coexisting conformers and structural transformations. In seeking to apply new techniques to the study of the biomolecular structure, this work builds upon the seminal experiments of Derrick and Williams and their coworkers who studied the nature of in-droplet processes for biomolecules using theta capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…This was accomplished while preserving biomolecular structures such as that demonstrated by the mass spectra for G‐quadruplex DNA ions, which were shown to be similar to those acquired using ESI under native conditions. The second advantage of cVSSI has been demonstrated recently, where the new ionization approach is shown to be a remarkably gentle technique allowing the preservation of solution structures for fragile proteins that may unravel during the ESI process 48 . A third attribute of cVSSI is its relative simplicity in that a droplet plume is generated in a straightforward fashion without the need for an auxiliary nebulization gas that would not allow facile in‐droplet HDX measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the development of cVSSI in 2019, several applications for mass spectrometry have been explored, including uses in droplet hydrogen/deuterium exchange, liquid chromatography, solid phase microextraction, and native biomolecule analysis. [28][29][30][31][32] Here, we present the rst application of cVSSI as a nebulization device for ICP-MS, and also discuss the fused deposition modeling (3D printing) of a sample introduction chamber to interface the cVSSI nebulization device with the ICP. Previous studies have shown the feasibility of using fused deposition modeling to create spray chambers for ICP-MS. Thompson demonstrated the ability to 3D model, print, and use cyclonic spray chambers for ICP optical emissions spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of cVSSI in 2019, several applications for mass spectrometry have been explored, including uses in droplet hydrogen/deuterium exchange, liquid chromatography, solid phase microextraction, and native biomolecule analysis. 28–32…”
Section: Introductionmentioning
confidence: 99%